HUBUNGAN BEBERAPA FAKTOR DENGAN KELENGKAPAN PENGISIAN BUKU KESEHATAN IBU DAN ANAK OLEH BIDAN DESA DI WILAYAH KERJA PUSKESMAS JEPARA TAHUN 2016 - Rosnaya Ari Sarasati; Atik Mawarni; Yudhy Dharmawan (Jurnal Kesehatan Masyarakat (Undip), 2016)
One effort to improve the quality of health care of mothers and children is completeness of MCH handbook. MCH handbook is a tool for early detection of disorder or maternal and child health issues. In Jepara district, the contents of MCH handbook were not complete and not filled, there were nutrition and feeding, Stimulation Detection and Early Intervention on Growth and Development and child health records. This study aims to analyze some factors related to the completeness of MCH handbook filling by a village midwives. This type of research was Explanatory Research with Cross Sectional Study. Study population was 16 village midwives and 1,001 mothers with 5 years old children and has a MCH handbook. Proportional random sampling was applied and obtained a sample of 16 village midwives and 88 MCH handbooks. Data analysis consisted of univariate, bivariate analysis using Rank Spearman and multivariate analysis using multiple linear regression. Results of univariate analysis showed that most of village midwives aged 35-39 years old (50%) with length of work in 11-20 years (56.3%), good enough knowledge (68.8%), good enough attitude (50%), less good motivation (37.5%), good enough skills (68.8%), good enough data requirement (43.8%), less complexity of form (50.0%). The results of the bivariate analysis showed that there are correlation between knowledge (rs = 0.488), attitude (rs = 0.317) and skills (rs = 0.329) with the completeness of MCH handbook filling by village midwives. Multivariate analysis showed that there are correlation between knowledge and skills with the completeness of MCH handbook filling by village midwives. Recommendation to Puskesmas Jepara are establish a training program about MCH handbook and how to filling MCH handbook that aims to improve the knowledge, attitude and skills of village midwives in filling of MCH handbook.